2013
DOI: 10.1016/j.vaccine.2013.03.052
|View full text |Cite
|
Sign up to set email alerts
|

Economic evaluation of vaccination programme of 13-valent pneumococcal conjugate vaccine to the birth cohort in Japan

Abstract: Japan is now preparing to incorporate PCV-7 into the national childhood immunisation programme. Our recently published economic evaluation of using PCV-7 to the birth cohort suggests that the cost to gain one QALY is lower than the WHO's cost-effectiveness criterion for intervention. However, many countries have started to introduce PCV-13 into their national immunisation schedule replacing PCV-7 for preventing pneumococcal diseases among young children. These raise the need to appraise the 'value for money' o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
28
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(28 citation statements)
references
References 20 publications
0
28
0
Order By: Relevance
“…In our analysis, herd protection was not assumed given that the analytical time horizon was restricted to child age cohorts. To our knowledge, the implications of herd protection have not been addressed in any of the cost-effectiveness analyses published for Japan [ 51 , 52 ]. Previous studies have examined the potential magnitude of such indirect effects including herd protection and serotype replacement [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…In our analysis, herd protection was not assumed given that the analytical time horizon was restricted to child age cohorts. To our knowledge, the implications of herd protection have not been addressed in any of the cost-effectiveness analyses published for Japan [ 51 , 52 ]. Previous studies have examined the potential magnitude of such indirect effects including herd protection and serotype replacement [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…The findings of this study extend the results of previous research on the economic burden of pneumococcal infection. Several cost-of-illness studies have been conducted in other countries; 13,[23][24][25] however, direct comparisons between these studies and the present study are difficult. The estimated burden of IPD (19.5 cases/100,000 individuals) and hospitalized pneumonia (17.4 cases/1,000 individuals) in this study is similar to reported rates in Hong Kong (23.7 cases/100,000 individuals and 931.6 cases/100,000 individuals, respectively) 26 and Japan (11.7 cases/ 100,000 individuals and 17.6 cases/1,000 individuals, respectively).…”
Section: Discussionmentioning
confidence: 82%
“…27 A comparison between the present study in Taiwan and studies in Japan may be feasible because of them have similar socioeconomic environments and approaches to healthcare delivery in these countries. 23,24 In this study, the estimated costs, including direct and indirect costs, were derived from data on the disease burden of pneumococcal infection with hospitalization according to detailed cost data. The annual direct costs associated with pneumococcal infection were estimated to be US $42.1 million for hospitals based on a birth cohort of 480,000 new born babies and assumed rates of 19.6 cases and 1,854.2 cases per 100,000 general pediatric hospitalizations related to IPD and pneumonia, respectively.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Both IPD and pneumococcal pneumonia cases were assumed to carry an age-specific risk of mortality based on published case fatality rates. [32][33][34][35][36] No risk of mortality was considered for AOM cases.…”
Section: Epidemiologic Parametersmentioning
confidence: 99%